번식기동안 백로과 조류의 종별 취식지 이용 - 이윤경(Yun-Kyoung Lee); 김동원(Dong-Won Kim); 장병순(Byoung-Soon Jang); 유승화(Seung-Hwa Yoo); 김창회(Chang-Hoe Kim); 강종현(Jong-Hyun Kang); 권인기(In-Ki Kwon); 류지은(Ji-Eun Ryu); 서재화(Jae-Hwa Suh); 서민환(Min-Hwan Seo); 박진영(Jin-Young Park) (한국조류학회지, 2012)
본 연구는 우리나라에서 집단으로 번식하는 백로과 조류 중 5종(왜가리 Ardea cinerea, 중대백로 A. alba, 쇠백로 Egretta garzetta, 황로 Bubulcus ibis, 중백로 E. intermedia)의 중요한 취식지유형을 알아보고, 종별 시기에 따른 취식지 이용의 변화를 파악하기 위해 수행되었다. 2011년 번식기(4월-7월)에 관찰한 백로과 조류는 총 5,806개체(왜가리 1,797개체, 중대백로 1,504개체, 쇠백로 680개체, 황로 1,281개체, 중백로 544개체)였으며, 가장 많은 개체수가 이용하는 취식지는 논(59%)으로 나타났고, 다음으로 하천, 갯벌, 저수지 등을 많이 이용하였다. 종별로 선호하는 취식지를 살펴보면, 왜가리는 하천(41%), 중대백로와 쇠백로는 논(53%, 58%)과 하천(33%, 28%), 황로와 중백로는 논(89%, 98%)을 주로 이용하였다. 다양한 서식지를 이용하는 왜가리, 중대백로, 쇠백로는 시기에 따라 논, 하천, 갯벌, 저수지 등의 이용 비율이 다르게 나타났고, 중백로는 시기와 상관없이 번식기간 내내 논을 주로 이용하였다. 본 조사결과에서 논과 하천은 번식기의 백로과 조류에게 중요한 취식지역이었다. 그러나 인간의 활동영역과 겹치는 이들 서식지는 환경이 급격하게변화하고 있으며, 이러한 변화가 백로과 조류의 번식에 어떤 영향을 끼치는지에 대한 조사가 이루어져야 할 것으로 판단된다. We investigated feeding habitats and seasonal uses of 5 species of colonial herons (Grey Herons Ardea cinerea, Great Egrets A. alba, Little Egrets Egretta garzetta, Cattle Egrets Bubulcus ibis, Intermediate Egrets E. intermedia) during the breeding season. A total of 5,806 individuals was inspected: 1,797 in Grey Herons, 1,504 in Great Egrets, 680 in Little Egrets, 1,281 in Cattle Egrets, and 544 in Intermediate Egrets. These herons foraged for food at rice fields (59%), rivers (26%), tidal flats (8%) or reservoirs (7%). The feeding habitat preference was different among species: rivers for Grey Herons, both rice fields and rivers for Great Egrets and Little Egrets, rice fields for Cattle Egrets and Intermediate Egrets. Grey Herons, Great Egrets, and Little Egrets used various habitats for feeding although the degree of the use of habitats was different according to seasons. On the other hand, Intermediate Egrets consistently used at rice fields for feeding regardless of seasons. Our study showed that the most significant feeding habitat of herons was rice fields and followed by rivers during the breeding season. However, these habitats which overlap with living space for humans have dramatically changed due to pressures for economic development in recent years. We need further long-term studies on the change of breeding populations of colonial herons to the environmental changes of important feeding habitats. KCI Citation Count: 8